Validation and Measurement Invariance of the Computer Attitude Measure for Young Students (Camys). (July 2014) - Asil, Mustafa; Teo, Timothy; Noyes, Jan
Students' attitudes toward technology, especially computers, play a key role in the effective integration of Information and Communication Technologies (ICT). Although numerous attitude scales have been developed to measure attitude toward computers, we found only a few instruments designed for young students aged 11–13 years. Among these attitude scales, the Computer Attitude Measure for Young Students (CAMYS) scale was developed specifically for use on young students. In this study, we examine whether CAMYS is still a valid and relevant instrument given the exponential changes in computer systems. Confirmatory factor analyses (CFA) and measurement invariance analyses across gender on sub-samples for cross validation were performed. Positive computer attitudes among the students were observed. The CFA results confirmed the existence of three separate factors: perceived ease of use (PEU), affect toward computer (ATC), and perceived usefulness (PU). The revised model was found to have a good fit and to show invariance across gender. We concluded that future research could use the revised scale for measuring computer attitudes of young students with confidence.